Temperature Dependence of the Leachability of Cemented Paste Backfill - Bull, Andrew (Université d'Ottawa / University of Ottawa, 2019)
Underground mining is a mineral acquisition technique that is critical to global economies, and human technological advancements. As shallow resource reserves are depleted, mine depths are increasing to accommodate global mineral demand. Increases in mine throughputs and excavation depths pose increased environmental concerns. Tailings surface disposal, and underground mine support are two considerable environmental and geotechnical factors of concern in current day mining. Underground waste disposal has been adopted by the mining industry in many forms. Cemented paste backfill (CPB) is a common best management practice developed to tackle these two specific resource industry related issues worldwide. CPB is a cement-stabilized material composed of tailings, water, and hydraulic binder. Tailings disposal areas on the earth’s surface are reduced by disposing of tailings in subsurface stopes that have been previously excavated. This increases underground safety by providing structural support to the mine. There are also economic benefits to this practice, as the additional support allows for adjacent pillars to be excavated. Although CPB greatly reduces tailings exposure to atmospheric elements, there are still underground environmental factors that must be considered with respect to environmental performance. CPBs are porous media, meaning they are susceptible to leaching of naturally occurring metals that are no longer in a stable condition as they were when incorporated in the parent rock. Arsenic and lead are metals of concern due to their association with many ore bodies. Leaching of these unstable metals may be influenced by the backfill curing temperature and the chosen hydraulic binder. Curing temperatures may be influenced by geographic location, local stope geology and depth, hydration and transport, among others. Hydraulic binders are chosen based on availability, cost, and desired mechanical properties of the paste. In this research, the effect of curing temperature and binder composition on the leachability of CPB are studied. ASTM C 1308 leaching protocol is used to determine the leachability of six CPBs. In addition, microstructural techniques (Powder X-Ray Diffraction, Mercury Intrusion Porosimetry, and Scanning Electron Microscopy) are used to relate the microstructural properties of the CPB to the leaching characteristics. Results reveal that CPBs cured with ordinary Portland cement (OPC) leach significantly less than CPBs cured with an OPC/Blast furnace slag (Slag) binder (50% blending ratio) as a result of CH consumption in slag hydration. Both CH and C-S-H are responsible for immobilizing arsenic in cement stabilized materials. OPC-CPBs contain greater relative quantities of CH, which aids in arsenic immobilization. Between the range of 2°C and 35°C OPC-CPB performed better at lower curing temperatures. Lower curing temperatures are favoured in OPC-CPB because the pore surface greater than the threshold pore diameter is reduced. Alternatively, OPC/Slag-CPB exhibited a decrease in cumulative mass leached at higher curing temperatures. The difference in cumulative mass leached by the OPC/Slag-CPBs is also related to the pore surface, and threshold pore diameter.
Keywords: Cemented Paste Backfill; Leachability; Arsenic; Waste Management; Temperature; Binder